TAFSIR QS. LUQMAN VERSE 12: Study of Analysis of Tafsir of Nusantara By K.H. Bisri Mustofa And Quraish Shihab - Mentari, Aswadan (HUNAFA Jurnal Studia Islamika, 2023)
This study is intended to explain the interpretation of QS. Luqman verse 12 is based on a comparative analytical study of the interpretation of the archipelago by K.H. Bisri Musthofa and Quraish Shihab. This research was made using the library study method. The results of this study show that the comparison between the interpretations written by Bisri Mustofa and Quraish Shihab is quite substantial. It has several similarities in the method and style of interpretation. In addition, there are several differences in the meaning of some words due to different sources of interpretation, the conditions of the community, and the time of the mufassir, which influenced his interpretation. This can happen because the pattern of these two interpretations is adab ijtima'i (social). Two different words interpret the word wisdom in this verse. Bisri Mustofa's interpretation only explains that Luqman received wisdom from Allah with a clear understanding of wisdom according to his view. Meanwhile, Quraish Shihab interprets wisdom as something that hinders. The point is that wisdom is something that, when used, can prevent and prevent damage or evil that will come and will create benefit. This difference occurs because of the two figures' thoughts and breadth of knowledge in understanding the meaning of a verse text of the Qur'an.